God's country: Christian Zionism in America - Goldman, Samuel (Haney foundation series, 2018)
"The United States is Israel's closest ally in the world. The fact is undeniable, and undeniably controversial, not least because it so often inspires conspiracy theorizing among those who refuse to believe that the special relationship serves America's strategic interests or places the United States on the right side of Israel's enduring conflict with the Palestinians. Some point to the nefarious influence of a powerful "Israel lobby" within the halls of Congress. Others detect the hand of evangelical Protestants who fervently support Israel for their own theological reasons. The underlying assumption of all such accounts is that America's support for Israel must flow from a mixture of collusion, manipulation, and ideologically driven foolishness. Samuel Goldman proposes another explanation. The political culture of the United States, he argues, has been marked from the very beginning by a Christian theology that views the American nation as deeply implicated in the historical fate of biblical Israel. God's Country is the first book to tell the complete story of Christian Zionism in American political and religious thought from the Puritans to 9/11. It identifies three sources of American Christian support for a Jewish state: covenant, or the idea of an ongoing relationship between God and the Jewish people; prophecy, or biblical predictions of return to The Promised Land; and cultural affinity, based on shared values and similar institutions. Combining original research with insights from the work of historians of American religion, Goldman crafts a provocative narrative that chronicles Americans' attachment to the State of Israel"--jacket flaps